Evaluating Social Enterprise Performance Measurement: A Sustainability Perspective - Nurindrasari, Diana; Ludigdo, Unti; Purwanti, Lilik; Mulawarman, Aji Dedi (Kompartemen : Jurnal Ilmiah Akuntansi, 2025)
This study aims to evaluate the performance measurement strategies used by social enterprises based on the 5Ps sustainability perspective of the SDGs. Multi-case study was used with involving in-depth interviews with five CEOs from diverse social enterprises operating over seven years in Indonesia. We found that social enterprises have integrated the 5Ps into their performance measurement implementation. However, in the process, social enterprises experience difficulties in identification and measurement due to the apparent barrier between performance and impact, which is abstract and difficult to predict. In response to this problem, social enterprises use quantitative and qualitative approaches. The implication of this research is in the form of strategic recommendations for social enterprises to achieve sustainability and sustainable development and meet the expectations of stakeholders for responsible business entity behavior.